A phase II study of Endostatin in combination with paclitaxel, carboplatin, and radiotherapy in patients with unresectable locally advanced non-small cell lung cancer. Issue 1 (December 2016) - Sun, Xiao-Jiang; Deng, Qing-Hua; Yu, Xin-Min; Ji, Yong-Lin; Zheng, Yuan-Da; Jiang, Hao; Xu, Ya-Ping; Ma, Sheng-Lin
Abstract Background Endostatin inhibits the pro-angiogenic action of basic fibroblast growth factor and vascular endothelial growth factor in different human cancers. This study assessed the efficacy of endostatin combined with concurrent chemoradiotherapy of non-small cell lung cancer (NSCLC). Methods Nineteen patients with unresectable stage III NSCLC, Eastern Cooperative Oncology Group (ECOG) performance status 0-l, and adequate organ function were treated with 60–66 Gy thoracic radiation therapy over 30–33 fractions concurrent with weekly 7.5 mg/m2 endostatin for 14 days, 50 mg/m2 paclitaxel, and 2 mg/mL/min carboplatin over 30 min. Patients were then treated with 7.5 mg/m2 endostatin for 14 days, 150 mg/m2 paclitaxel, and 5 mg/mL/min carboplatin every 3 weeks for 2 cycles as the consolidation treatment. The objective response rate was recorded according to the Response Evaluation Criteria in Solid Tumors (RECIST) criteria, and the toxicity was evaluated using the National Cancer Institute (NCI) Common Toxicity Criteria. Results Six patients were unable to complete the consolidation treatment (4 pulmonary toxicity, 1 tracheoesophageal fistulae, and 1 progressive disease). Seventeen patients were included for data analysis. Specifically, one (5.9 %) patient had a complete response and 12 (70.6 %) had a partial response, whereas two patients had stable disease and the other two had disease progression. The overall response rate was 76 % (95 % confidence interval [CI], 51 %–97 %). The median progression-free survival was 10 months (95 % CI, 7.6–12.3 months), and the median overall survival was 14 months (95 % CI, 10.7–17.2 months). Early 10 patients who completed the treatment regimen showed that four patients experienced grade III pulmonary toxicity a few months after chemoradiotherapy, leading to the early closure of the trial according to the study design. Conclusions The reslult of concurrent endostatin treatment with chemoradiotherapy in locally advanced unresectable NSCLC did not meet the goal per study design with unacceptable toxicity. The real impact of endostatin as the first-line treatment combined with chemoradiotherapy on the survival of NSCLC patients remains to be determined. (NCT 01158144).